A Systems Thinking Approach to Understanding and Demonstrating the Role of Peer-Led Programs and Leadership in the Response to HIV and Hepatitis C: Findings From the W3 Project - Brown, Graham; Reeders, Daniel; Cogle, Aaron; Madden, Annie; Kim, Jules; O'Donnell, Darryl (Frontiers in Public Health, 2018)
The central role of community and peer-led programs has been a key characteristic of the Australian partnership response to HIV and hepatitis C since the beginning of the epidemics. Despite this, peer-led programs continue to have limited capacity to demonstrate their role and value as part of a multi-sectoral response. What makes one peer-led program a better investment than another? What role does the rest of the sector have in ensuring we gain the most value from these investments? To investigate this, we facilitated interactive systems thinking methods with 10 programs working within communities of people who inject drugs, gay men, sex workers and people living with HIV across Australia. This included articulating program theories in diagram and textual form to help us understand the role of peer-based programs promoting peer leadership within the Australian HIV and hepatitis C responses. Our aim was to develop a framework for monitoring and evaluation that could be applied to peer led programs at different levels and in different contexts. We found that for peer-led programs to fulfill their role, and to navigate the rapid changes occurring in the both epidemics, they need to: demonstrate the credibility of their peer and community insights; continually adapt to changing contexts and policy priorities in tandem with their communities; and maintain influence in both community and policy systems. We developed a framework of four key functions (Engagement, Alignment, Adaptation, and Influence) which peer-based programs need to demonstrate, which form the basis for identifying quality indicators. This article presents a new way of framing and monitoring investments in peer-led programs and peer eadership actions by these programs. If health policy is committed to strengthening the leadership shown by affected communities, then we need to understand, enhance, monitor and value the role of peer-led programs and peer leadership within the overall prevention system. We believe the W3 framework, drawing on systems thinking and modeling, can support funders, policy-makers and programs to achieve this.